Etiology and Antimicrobial Susceptibility of Pathogens Associated with Urinary Tract Infections among Women Attending Antenatal Care in Four South African Tertiary-Level Facilities, 2015–2019 - Thembekile Zwane; Liliwe Shuping; Olga Perovic (Antibiotics, 2021)
In South Africa, uncomplicated community-acquired UTIs (CA-UTIs) are treated empirically; however, the extent of antibiotic resistance among these pathogens is not well known. We conducted a descriptive cross-sectional study of women attending ANCs at four tertiary public-sector hospitals in Gauteng. Female patients aged 15–49 years, with urine cultures performed between January 2015 and December 2019, were included. A case of culture-confirmed UTI was defined as any woman with ≤2 uropathogens with a bacterial count of ≥105 colony-forming units per ml for at least one pathogen. We identified 3558 cases of culture-confirmed UTIs in women with a median age of 30 years (interquartile range; 25–35). E. coli accounted for most infections (56% (1994/3558)), followed by E. faecalis, with a prevalence of 17% (609/3558). The prevalence of K. pneumoniae was 5% (193/3558), 5% (186/3558) for S. agalactiae, and 5% (179/3558) for P. mirabilis. Ninety-five percent (1827/1927) of the E. coli and 99% of the E. faecalis (301/305) isolates were susceptible to nitrofurantoin. Common uropathogens showed high susceptibility to first-line antibiotics, gentamicin and nitrofurantoin, as recommended for use in primary healthcare settings. Overall, our study provided an indication of the level of antimicrobial resistance in the four facilities.